2004
DOI: 10.1039/b406804c
|View full text |Cite
|
Sign up to set email alerts
|

Highly stereoselective oxy-Michael additions to α,β-disubstituted nitro olefins: asymmetric synthesis of pseudo-norephedrine derivatives and THP* protected α-hydroxy ketones

Abstract: The "naked" anion of (S)-6-methyl delta lactol undergoes efficient oxy-Michael addition to alpha,beta-disubstituted nitro olefins to give the THP* protected Henry products with excellent (95-->98% de) stereocontrol at the beta-position and moderate (up to 3 : 1) stereocontrol at the alpha-position in favour of the syn-diastereoisomer. Nitro group reduction with in situN-Boc protection and THP* removal provides alpha,beta-disubstituted ethanolamine derivatives, while treatment with tetrapropylammonium perruthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
6
8
0
Order By: Relevance
“…Addition of the Michael acceptors 2 (0.67 equiv) and stirring for 1 hour before quenching with acetic acid (2.0 equiv) at -78 °C afforded, after aqueous work-up, the crude oxy-Michael adducts 3 with high stereoselectivity at the b-centre (up to 94%), and, for the major diastereoisomer at the b-centre, moderate selectivity at the a-centre (syn/anti from 2.1:1 to 3:1; Table 1). 22 The high facial selectivity on addition to the nitro olefin acceptor is consistent with our previous observations; [16][17][18][19][20] likewise the moderate syn/anti selectivity, in favour of the syn diastereoisomer, resulting from the acetic acid quench of the reaction mixture has been observed previously. 18 Interestingly, the geometry of the double bond in the Michael acceptor has little-to-no bearing on the observed stereoselectivity at the b-centre in the oxy-Michael addition; different ratios of Z/E isomers ( Table 1, entries 2 vs. 3 and 9 vs. 10) lead to similar de (b) values.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Addition of the Michael acceptors 2 (0.67 equiv) and stirring for 1 hour before quenching with acetic acid (2.0 equiv) at -78 °C afforded, after aqueous work-up, the crude oxy-Michael adducts 3 with high stereoselectivity at the b-centre (up to 94%), and, for the major diastereoisomer at the b-centre, moderate selectivity at the a-centre (syn/anti from 2.1:1 to 3:1; Table 1). 22 The high facial selectivity on addition to the nitro olefin acceptor is consistent with our previous observations; [16][17][18][19][20] likewise the moderate syn/anti selectivity, in favour of the syn diastereoisomer, resulting from the acetic acid quench of the reaction mixture has been observed previously. 18 Interestingly, the geometry of the double bond in the Michael acceptor has little-to-no bearing on the observed stereoselectivity at the b-centre in the oxy-Michael addition; different ratios of Z/E isomers ( Table 1, entries 2 vs. 3 and 9 vs. 10) lead to similar de (b) values.…”
supporting
confidence: 91%
“…Our group and others 15 have been involved with the development of chiral water equivalents for the addition to reactive Michael acceptors and to this end the highly diastereoselective oxy-Michael addition of the 'naked' anions of enantiopure delta lactols has been described. We recently found that the addition of the 'naked' anion of (S)-6-methyl tetrahydropyran-2-ol (1) to b-substituted nitro olefins proceeded with high diastereoselectivities and yields 16 and this methodology has been successfully applied to other Michael acceptors such as malonate derivatives, 17 a,b-disubstituted nitro olefins, 18 a,b-unsaturated methylsulfone-derived acceptors 19 and in the synthesis of bioactive compounds. 20 We believed that an extension of this methodology to encompass the synthesis of protected b-aryl-b-hydroxy-a-amino acids would further highlight the power of this work.…”
mentioning
confidence: 98%
“…After reduction of the nitro group and protection of the resulting amine, the lactol moiety is cleaved by use of a polymer -bound acid resin, which avoids any reduction in the enantiomeric purity of the obtained N -Boc amino alcohol 39 . Application of these procedures to α , β -disubstituted nitroalkenes results in modest control of the newly created α -stereocenter and excellent control at the β -position, with a moderate preference for the syn stereoisomer [42,43] .…”
Section: Amino Alcoholsmentioning
confidence: 99%
“…[12] This reaction has been extended to a range of Michael acceptors [13] and has found use in the syntheses of biologically active b-amino alcohols. [14] The high C6-C2 stereocontrol has also been observed in the reactions of the corresponding potassium salts with alkyl and acyl halides and with acetic anhydride.…”
Section: Introductionmentioning
confidence: 99%